Human-in-the-Loop : Probabilistic Modeling of an Aerospace Mission Outcome - Suhir, Ephraim; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Improvements in safety in the air and in space can be achieved through better ergonomics, better work environments, and other efforts of the traditional avionic psychology that directly affect human behaviors and performance. Not limited to just the aerospace field, this book discusses adaptive probabilistic predictive modeling in human-in-the-loop situations. This involves situations where human performance and equipment reliability contributes jointly to the success and safety of a mission. This book gets you familiar with a new, powerful, flexible, and effective approach to making outcomes from missions successful and safe.
1. Introduction: Probabilistic Modeling Approach in Aerospace Engineering -- 2. Fundamentals of Applied Probability -- 3. Helicopter-Landing-Ship and the Role of the Human Factor -- 4. Fundamentals of Probabilistic Aerospace Electronics Reliability Engineering -- 5. Probabilistic Assessment of an Aerospace Mission Outcome -- 6. The "Miracle-on-the-Hudson" Event: Quantitative Aftermath -- 7. "Two Men in a Cockpit": Likelihood of a Casualty If One of the Pilots Gets Incapacitated -- 8. Probabilistic Modeling of the Concept of Anticipation in Aviation -- 9. Double-Exponential Probability Distribution Function for the Human Nonfailure.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY & ENGINEERING / Quality Control; DEPDF; Double-Exponential Probability Distribution Function; PPM; Probabilistic Predictive Modeling; SA; Sensitivity Analysis; Aeronautics -- Human factors; Systems engineering -- Simulation methods; Probabilities; TECHNOLOGY & ENGINEERING -- Engineering (General); Electronic books